Netnography Study on @bibit.Id Instagram Account as a Digital Literature Fund Investment - Nada Nadhifah Kamilia; Edy Prihantoro (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The growing use of social media is used not only for personal gain but also as a place to gain new knowledge. This research was conducted to explain how Bibit's use of Instagram social media is a digital literacy medium regarding mutual fund investment. As a mutual fund investment marketplace, Bibit takes advantage of its role to educate the public about mutual fund investment so that they are motivated to start investing so that they can increase the number of local investors. This study uses a netnography method so that observations on the subject of the research object and data collection are carried out online. The results of this study indicate that Bibit uses its Instagram account to educate its audience about mutual fund investment through educational content in the form of illustrated images and videos with a microblogging content style. This study concludes that Bibit chose Instagram as a digital literacy medium for mutual fund investment. His audience is the right choice because Instagram has features that help convey information efficiently. In addition, Instagram has many users and easy access.